Reflecting the Value of Character Education in Lesson Planning - Panggabean, Justice Zeni Zari (Universitas Pendidikan Ganesha, 2022)
Changes in the curriculum and its tools require competent teachers to make lesson plans. Teachers also provide challenges as educational actors who internalize character values through lesson planning. This study aimed to analyze the reflection of character education carried out by teachers in learning planning. This study uses a descriptive quantitative design with a survey model to collect documents related to the object under study. The sampling method was used to determine the participants who found 11 people. Data collection was carried out using observation techniques using instruments containing a statement of the indicator numbers produced, valid for as many as 20 statement items. The data processing technique uses a parametric calculation application. The results showed that elementary school teachers' reflection of character education in lesson planning had been implemented to invite students' awareness in responding as much as 45.55%. The conclusions in this study indicate that the teacher's character has an important role to be used as an example in the inculcation of character values so that it is possible to apply character values in learning planning to make it easier for teachers to integrate character values in learning.